Modal Intelektual, Nilai Perusahaan, dan Kinerja Keuangan Sebagai Variabel Intervening - Sutrisna Yanti, Desak Nyoman; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 34 No 9 (2024), 2024)
The aim of this study is to obtain empirical evidence of the influence of intellectual capital on financial performance, the influence of intellectual capital and financial performance on corporate value, as well as the influence of financial performance as a mediation variable on the relationship between intellectual capital and corporate value in food and beverage sub-sector companies listed on the IDX. The population in this study is all food and beverage industry companies listed on the Indonesia Stock Exchange in 2015-2019. The number of samples used as many as 18 companies with a research period of five years, namely 2015 to 2019, bringing the total observation data obtained as many as 90. The data analysis technique used is multiple linear analysis.  The results of the analysis showed that Intellectual Capital (VAICTM) had a positive and significant effect on financial performance (ROE), Intellectual Capital (VAICTM) and financial performance (ROE) had a positive and significant effect on the Company's Value (PBV), as well as financial performance was able to mediate the relationship between Intellectual Capital (VAICTM) to Corporate Value (PBV). Keywords : Intellectual capital, financial performance, corporate value